Campylobacter jejuni Pericarditis: A Case Report - Neves-Maia, Joao (2022)
Campylobacter jejuni is one of the most common causes of enteritis. In rare cases, extraintestinal infection can occur, with a handful of cases of cardiac involvement, of which the pathophysiological mechanism is unclear. We report a case of pericarditis in a patient with X-linked agammaglobulinemia presenting with chronic diarrhea and chest pain who evolved to cardiac tamponade, requiring a pericardial window and a long course of broad-spectrum antibiotics. To the best of our knowledge, this is the third case of pericarditis caused by Campylobacter jejuni reported in the literature, the second in a patient with X-linked agammaglobulinemia. Despite its rarity, this case serves as a reminder of Campylobacter as a potential cause of cardiac inflammation for clinicians treating pericarditis/myocarditis, especially in patients with a history of diarrhea or immunosuppression.